As given by the question
There are given that the system of the equation:
![\begin{gathered} -3x+7y=-16\ldots(1) \\ -9x+5y=16\ldots(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m8dalpfun31ysotb1yvzisnfxqc8vrla8r.png)
Now,
From the equation (1):
![\begin{gathered} -3x+7y=-16 \\ -3x=-16-7y \\ x=(16)/(3)+(7)/(3)y\ldots(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w1nian04a25l6hrfo7uberr5vovt4leppt.png)
Put the value of equation (3) into equation (2)
So,
![\begin{gathered} -9((16)/(3)+(7)/(3)y)+5y=16 \\ -3(16+7y)+5y=16 \\ -48-21y+5y=16 \\ -48-16y=16 \\ -16y=64 \\ y=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dv8rdgdp7hqeimrfebz6hl8o63uilordcc.png)
Then,
Put the value of y into the equation (3)
So,
![\begin{gathered} x=(16)/(3)+(7)/(3)y \\ x=(16)/(3)+(7)/(3)(-4) \\ x=(16)/(3)-(28)/(3) \\ x=(16-28)/(3) \\ x=-(12)/(3) \\ x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3kb22xgqs1lzqjhfsi0ij5snb0hfs494c2.png)
Hence, the value of x is -4 and the value of y is -4.